A Review on Currently Available Potential Therapeutic Options for COVID-19 - Ohadian Moghadam S (International Journal of General Medicine, 2020)
Solmaz Ohadian Moghadam Uro-Oncology Research Center, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Solmaz Ohadian MoghadamUro-Oncology Research Center, Tehran University of Medical Sciences, Tehran, IranTel/ Fax +98 21 66 43 77 25Email s-ohadian@sina.tums.ac.irAbstract: A series of unexplained pneumonia cases currently were first reported in December 2019 in Wuhan, China. Official names have been announced for the virus responsible, previously known as “ 2019 novel coronavirus” and the diseases it causes are, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and coronavirus disease (COVID-19), respectively. Despite great efforts worldwide to control SARS-CoV-2, the spread of the virus has reached a pandemic. Infection prevention and control of this virus is the primary concern of public health officials and professionals. Currently, several therapeutic options for COVID-19 are proposed and vaccine development has been initiated for prevention purposes. In this review, we will discuss the most recent evidence about the current potential treatment options including anti-inflammatory drugs, angiotensin-converting enzyme inhibitors/angiotensin receptor blockers, nucleoside analogs, protease inhibitors, monoclonal antibodies, and convalescent plasma therapy. Some other agents such as vitamin D and melatonin, which were recommended as potential adjuvant treatments for COVID-19 infection are also presented. Moreover, the potential use of convalescent plasma for treatment of COVID-19 infection was described. Furthermore, in the next part of the current review, various vaccination approaches against COVID-19 including whole virus vaccines, recombinant subunit vaccine, DNA vaccines, and mRNA vaccines are discussed.Keywords: COVID-19, SARS-CoV-2, treatment, vaccine, coronavirus